1983
DOI: 10.1073/pnas.80.3.790
|View full text |Cite
|
Sign up to set email alerts
|

Grass leaf silicification: Natural selection for an inducible defense against herbivores

Abstract: Plants from four populations of three species of African grasses were collected from grasslands in Tanzania's Serengeti National Park that differ in the grazing intensity that they experience. Plants were grown in the laboratory in a factorial experiment in which variables were plant origin, species identification ofplants, defoliation intensity, and supply of soluble silicate in the nutrient medium. All plants accumulated silica in leafblades in the absence of soluble silicate from the nutrient medium. Plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
152
1
4

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(162 citation statements)
references
References 16 publications
5
152
1
4
Order By: Relevance
“…Several other physical plant defenses have been shown to be inducible, including structural silica (McNaughton and Tarrants 1983), tree gum (Karban 1983), and leaf toughness (Schultz and Baldwin 1982). These physical defenses are mostly irreversible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other physical plant defenses have been shown to be inducible, including structural silica (McNaughton and Tarrants 1983), tree gum (Karban 1983), and leaf toughness (Schultz and Baldwin 1982). These physical defenses are mostly irreversible.…”
Section: Discussionmentioning
confidence: 99%
“…Induced resistance to insect attack has been inferred from increased production of chemical or physical defenses, or reduced fitness of herbivorous insects (Rhoades 1983; Schultz and Baldwin 1982;McNaughton and Tarrants 1983;Karban 1983;Karban and Carey 1984). Such plasticity in plant defenses allows plants to divert resources to defense only when they are needed, increasing overall efficiency of resource allocation.…”
Section: Abstract: Induced Defense -Herbivorymentioning
confidence: 99%
“…To date, only two studies have found evidence for induction of silica (McNaughton and Tarrants 1983;McNaughton et al 1985). This may be due to the fact that most studies examining potential damage-induced silica deposition in grass leaves have tested induction in response to mechanical damage (McNaughton and Tarrants 1983;McNaughton et al 1985;Brizuela et al 1986;Cid et al 1989;Cid et al 1990;Banuelos and Obeso 2000).…”
mentioning
confidence: 95%
“…This may be due to the fact that most studies examining potential damage-induced silica deposition in grass leaves have tested induction in response to mechanical damage (McNaughton and Tarrants 1983;McNaughton et al 1985;Brizuela et al 1986;Cid et al 1989;Cid et al 1990;Banuelos and Obeso 2000). It has long been known that artificial Hartley and Lawton 1991).…”
mentioning
confidence: 99%
“…With the exception of McNaughton & Tarrants (1983), no studies have attempted to place elemental plant defences into either category. McNaughton & Tarrants (1983) showed that silica contents of several African savanna grass species increased after exposure to simulated herbivory treatments ; thus, they considered silicification to be an inducible defence. The response of foliar metal concentrations of hyperaccumulators to herbivore damage has not been determined.…”
mentioning
confidence: 99%